Commensurate Nb2Zr5O15: Accessible Within the Field Nb2ZrxO2x+5 After All. Issue 4 (4th April 2019) - Wiedemann, Dennis; Orthmann, Steven; Mühlbauer, Martin J.; Lerch, Martin
Abstract: Doped niobium zirconium oxides are applied in field‐effect transistors and as special‐purpose coatings. Whereas their material properties are sufficiently known, their crystal structures remain widely uncharacterized. Herein, we report on the comparably mild sol‐gel synthesis of Nb2 Zr5 O15 and the elucidation of its commensurately modulated structure via neutron diffraction. We describe the structure using the most appropriate superspace as well as the convenient supercell approach. It is part of an α ‐PbO2 ‐homeotypic field with the formula Nb2 Zr x O2 x +5, which has previously been reported only for x ≥5.1, and is closely related to the structure of Hf3 Ta2 O11 . The results, supported by X‐ray diffraction and additional synthesis experiments, are contextualized within the existing literature. Via the sol‐gel route, metastable Nb−Zr−O compounds and their heavier congeners are accessible that shed light on possible structures of these commercially utilized materials. Abstract : Teaching an old dog neu ‐trons : The commensurately modulated Nb2 Zr5 O15 is not, as previously supposed, inaccessible. Synthesis is possible via a sol‐gel route under relatively mild conditions. X‐ray diffraction may be unable to elucidate its rather complex structure, but neutron diffraction sure can – with a little help from an initial model.